Enhanced scheme for context transfer in mobile multicast - Azana Hafizah bt Mohd Aman (Kulliyyah of Engineering, International Islamic University Malaysia, 2011)
Mobile networking environments have been developing very rapidly. Due to its dynamic nature and imprecise network state information, there are many challenges which need to be addressed especially the need for performance improvement to support mobile multicast. Multicast is defined as the delivery of data to a set of selected receivers. When a mobile node (MN) moves to a new subnet it needs to continue certain services that have already been established at the previous subnet. It is a difficult problem to maintain simplicity and reachability of a MN when moving (handover) from one network to another. Context Transfer Protocol (CXTP) gives support of the seamless handover based on service continuation using context. It aims to contribute to the enhancement in handover performance and proposed for MN for quickly re-establishment of their services when the nodes move and change their access routers. Numerous approaches have been proposed including Hierarchical Mobile IPv6 (HMIPv6) in order to provide better performance. It is mainly proposed to enhance the existing Mobile IPv6 (MIPv6). HMIPv6 adds new node called Mobile Anchor Point (MAP) to cater mobility problems of MIPv6. However to support multicast traffic HMIPv6 has its own problems. This thesis introduces an enhanced scheme that aims to improve the performance of the mobile node during handover in a multicast session. It integrates M-HMIPv6 with Context Transfer Protocol (CXTP). This results in reducing the mobile node's service recovery time, total signaling cost, handover latency and packet loss. The proposed scheme is implemented using NS-2 simulator. The evaluation of the proposed scheme is via simulation and mathematical analysis. The performance metrics used for the simulation are handover latency, and packet loss. On the other hand the performance metrics considered for the mathematical analysis are service recovery time and total signaling cost. The proposed scheme is benchmarked with the standard HMIPv6. The proposed scheme offers 80% better handover latency, 40% lower packet loss rate, 50% lower service recovery time and 89% better total signaling cost than the benchmarked scheme.